Association Between Air Conditioning Use and Self-reported Symptoms During the 2018 Heat Wave in Korea - Yong-Han Lee; Sanghyuk Bae; Seung-sik Hwang; Jong-Hun Kim; Kyoung-Nam Kim; Youn-Hee Lim; Miji Kim; Sohwa Jung; Ho-Jang Kwon (Korean Society for Preventive Medicine, 2020)
Objectives The purpose of this study was to investigate the health effects of air conditioning use during the 2018 heat wave in Korea, included the highest temperature ever recorded in the nation. Methods The participants in this study were 1000 adults aged 19 years and older recruited from across Korea. The participants were asked about their experience of symptoms of various diseases, disruptions of their daily lives, and use of air conditioning during the heat wave. The associations between air conditioning use during the heat wave and health outcomes were analyzed using the chi-square test and multiple logistic regression models. Results Among participants who lacked air conditioning in the main space where they spent time outside the home, 33.9%, 8.1%, 43.5%, and 19.4% experienced symptoms of heat-related, cardiovascular, nervous system diseases, and air-conditioningitis, respectively. In comparison, participants who did have air conditioning outside the home experienced the same symptoms at proportions of 21.0%, 1.9%, 26.8%, and 34.2%, respectively (p=0.027, 0.007, 0.007, and 0.023, respectively). Among participants who had no air conditioner at home, 10.0% were absent from school or work due to the heat wave. In contrast, among participants who had an air conditioner at home, only 3.7% were absent as a result of the heat wave (p=0.007). Conclusions When air conditioning was not used at home or in the main space where participants spent time outside the home during the 2018 heat wave, adverse health effects were more prevalent, but the risk of air-conditioningitis was reduced.